The effect of TIG arc brazing current on interfacial structure and bonding strength of tin-based babbit. Issue 21 (2nd November 2017) - Zhou, Fangming; Zhang, Qingya; Shi, Mingxiao; Guo, Junwu; Li, Hui
Abstract: The interfacial structure of the tin-based babbit obtained by TIG arc brazing was studied through the OM, XRD, SEM and EDS and the bonding strength was investigated by the Electronic Universal Testing Machine. It can be found that interfacial layers, unequal in thickness, ranged from 10.26 to 34.27 μm and IMCs layers formed at the interface, ranged from 1.5 to 4 μm as the welding current increased from 50 to 90 A. Also, the bonding strength apparently increased from 73 to 155 Mpa and shear fractures which occurred at the interface near iron substrate side were mainly brittle cleavage fracture. On the brazed interface, the higher element concentration of Fe was helpful to promote the metallurgical reaction and ensured the bonding property. The phase constituents of IMCs were FeSn, FeSn2 and Fe3 Sn2 . Moreover, the FeSn layer was plate shape, FeSn2 layer and Fe3 Sn2 layer were branched shape which staggered with the plastic Sn-based solid solution so that the bonding strength was improved. Physical model of the Fe–Sn IMC layers formation mechanism was proposed, the experimental results further showed that the model was scientific and effective.